RELATIONSHIP BETWEEN THE LEVEL OF KNOWLEDGE OF COVID-19 AND THE LEVEL OF KNOWLEDGE OF THE MOVEMENT CONTROL ORDER (MCO) TO BREAK THE COVID-19 INFECTION CHAIN AMONG PATIENTS WHO COME TO SEEK TREATMENT AT THE OUTPATIENT DEPARTMENT (OPD) KINARUT HEALTH CLINIC DURING THE MOVEMENT CONTROL ORDER (MCO) IS IMPLEMENTED - Baidi Baddiri; Mohd Khairuddin Abdullah @ Jerry Abdullah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The country has been facing the Covid-19 crisis that has affected the rest of the world in this decade. Numerous approaches and alternatives are implemented by the government in order to overcome this pandemic either controlled or stopped utterly. In order for the government to succeed, the emphasis on breaking the chain of infection of Covid-19 and the direction of the Movement Control Order (MCO) must be strengthened. Thus, the main goal of this study is to identify the level of patient’s knowledge regarding Covid-19 and Movement Control Order (MCO) as well as to analyse the relationship between the level of knowledge about Covid-19 and Movement Control Order (MCO) among patients who come for treatment at the Kinarut Health clinic. This study applies the quantitative research methodology, specifically surveys through questionnaires, whereas the sampling method used is convenient sampling with a total of 200 patients involved within the Kinarut area. Analysis of instrument evaluation and sampling technique is also discussed in this study. The results showed that the level of knowledge of the patients about Covid-19 was at a moderate level with a mean value = 3.610, SP = 0.345. The level of knowledge relating to Movement Control Order (MCO) is also at a moderate level with a mean value = 3.610, SP = 0.345. Meanwhile, correlation analysis showed that there is a strong relationship between the level of knowledge about Covid-19 and also the level of knowledge of the Movement Control Order (MCO), with a correlation value of r = 0.71, p> 0.05. Thus, the results of this analysis show that there is a strong relationship between the variables of the knowledge level of Covid-19 and Movement Control Order (MCO) in breaking the chain of infection Covid-19 particularly among patients living around Kinarut.